PROJECT MANAGEMENT ANALYSIS OF COMMUNITY BASED SANITATION ACTIVITIES IN LANGKAT REGENCY - Abdilah Ragilia M; Wahyu Ario Pratomo; Rulianda Purnomo Wibowo (CV. RADJA PUBLIKA, 2025)
This study analyzes project management practices and proposes strategic recommendations to minimize time addendums in the implementation of the Community-Based Sanitation (Sanimas) activities in Langkat Regency. Sanimas, initiated by the Ministry of Public Works and Housing, aims to expand access to proper sanitation through community participation. Despite its achievements, the program has faced execution challenges, particularly related to time constraints under the self-managed construction model. The research employs the Critical Path Method (CPM) to identify key activities affecting project duration. Findings indicate that delays in procurement and construction stages significantly contributed to the extension of project timelines beyond the stipulated 90 days. The total project duration based on the CPM analysis was found to be 47 days for critical path activities. This study recommends strengthening the capacity of Community-Based Implementation Team, enhancing coordination with stakeholders, integrating risk-based scheduling, and institutionalizing post-project evaluations. These strategic improvements are essential for ensuring timely and efficient implementation of future Sanimas projects.